Treatment of haemophilia in the elderly - Miesbach, W.; Krekeler, S.; Alesci, S. (Hämostaseologie, 2009)
Treatment of elderly patients with haemophilia is an upcoming challenge in haemophilia care. We included patients with haemophilia A older than 60 years of age, who visited our haemophilia centre between 2006 and 2008. We conducted a retrospective study focussing on the patients’ co-morbidities as well as changes in their bleeding patterns between 2003 and 2008. Results: There is a tendency of increasing bleeding symptoms with increasing age of the patients due to more frequent spontaneous joint bleedings, malignancies or treatment with phenprocoumon or ASS. In consequence, FVIII dosage had to be increased for 8 patients (28%). Chronic hepatitis C, coronary heart disease and malignancies are the most frequent co-morbidities
Keywords: Haemophilia A; co-morbidity; ageing